Adverse clinical events in the hospital: characterization from the point of view of the health worker. - González-González, Abel; Domínguez Osorio, Isabel; Quero Palomino, Verónica; León Velasco, Magdalena; Polo Montres, Filomena; Lasso Ruales, Ximena Tatiana; Alonso, Lidia Martín (Medicina Clínica y Social, 2022)
Introduction: an adverse event is an incident that has caused harm to a patient and that may or may not be associated with a clinical error. A high percentage of health professionals are involved in this type of event annually. A large part of the professionals are unaware of the existence of the systems implemented in their work centers for a correct communication of adverse events. Objectives: to identify the characteristics of hospital professionals affected by an adverse event and to evaluate their knowledge of the notification systems. Methods: cross-sectional descriptive observational study. Demographic, labor and related variables with adverse events and notification systems were evaluated. Results: 207, 45.4% nurses and 54.6% doctors, participated, 39.24 ± 10.07 years and with an experience of 14.43 ± 9.9 years. 71.8% were affected by some adverse event. The first adverse event occurred at 6.45 ± 6.18 years. 42.1% knew of some notification system; but only 24.61% of these, affected by an adverse event, reported it. Physicians were more affected by an adverse event, moreover earlier (p <0.001) and they were also more aware of notification systems (p = 0.001). Discussion: many health workers, with little experience, were affected by adverse events. Few knew notification systems and far fewer used them. Doctors were more affected, and earlier, by adverse events and were better acquainted with notification systems.